2012
DOI: 10.1002/ijc.27379
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for chemotherapy‐induced alopecia in mice using parathyroid hormone agonists and antagonists linked to a collagen binding domain

Abstract: Parathyroid hormone (PTH) agonists and antagonists have been shown to improve hair growth after chemotherapy; however, rapid clearance and systemic side-effects complicate their usage. To facilitate delivery and retention to skin, we fused PTH agonists and antagonists to the collagen binding domain (CBD) of Clostridium histolyticum collagenase. in-vitro studies showed that the agonist fusion protein, PTH-CBD, bound collagen and activated the PTH/parathyroid hormone-related peptide receptor in SaOS-2 cells. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
32
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 39 publications
8
32
0
1
Order By: Relevance
“…Meanwhile, either a ␤-branched residue or Leu is found at the position equivalent to Thr957 in most of the CBDs. Six other residues identified by 15 N-HSQC-NMR titration to interact with minicollagen are not well conserved. Since divergent CBDs (s3 and s3b) adopted a similar cleft-shaped binding pocket, other CBDs may also adopt a similar collagen-binding structure.…”
Section: Figmentioning
confidence: 96%
See 2 more Smart Citations
“…Meanwhile, either a ␤-branched residue or Leu is found at the position equivalent to Thr957 in most of the CBDs. Six other residues identified by 15 N-HSQC-NMR titration to interact with minicollagen are not well conserved. Since divergent CBDs (s3 and s3b) adopted a similar cleft-shaped binding pocket, other CBDs may also adopt a similar collagen-binding structure.…”
Section: Figmentioning
confidence: 96%
“…The s3b binds to collagenous peptides with triple-helical conformation but not to the similar peptides lacking triple-helical conformation or to gelatin (denatured collagen), suggesting that the CBD-collagen interaction is conformation specific (4,7). The most recent solution studies of s3b in complex with collagenous peptides by smallangle X-ray scattering (SAXS) and heteronuclear single quantum coherence (HSQC) nuclear magnetic resonance (NMR) titration of various spin-labeled collagenous peptides to 15 N-labeled s3b showed that s3b binds unidirectionally to the C terminus of collagenous peptides (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The PTH(7-34)-CBD and PTH-CBD subcutaneous injection in mice initially resulted in whole-animal distribution and, later, was followed by the redistribution of applied peptides to collagen-rich tissues such as bone and skin. No symptoms of hyperparathyroidism or calcium serum level alterations were found in the study [88]. The majority of hairs in the histopathological samples of treated mice stayed long in anagen VI, confirming the very potent role of the peptides used.…”
Section: Ppr Agonists and Antagonists As A Potential Treatment Optionmentioning
confidence: 73%
“…A single dose of the peptide PTH(1-33) caused a hair regrowth in mice within 30 days and an increase in the number of anagen phase VI hair follicles. Surprisingly, PTH-CBD antagonists have no significant effect on hair growth [88]. In another study, PTH agonists and antagonists were CBD-linked and applied subcutaneously to mice treated with cyclophosphamide.…”
Section: Ppr Agonists and Antagonists As A Potential Treatment Optionmentioning
confidence: 99%